Organic chemistry frontiers : an international journal of organic chemistry - Shanghai you ji hua xue yan jiu suo; Zhongguo hua xue hui (Beijing, China); Royal Society of Chemistry (Great Britain) (RSC Publishing, 2014)
Organic Chemistry Frontiers is a high impact journal publishing work on all disciplines of organic chemistry. The journal welcomes articles which make a significant contribution to the field of organic chemistry by reporting either new or significantly improved protocols or methodologies.
Keywords: Chemistry, Organic : Periodicals; Chemistry, Organic